Service quality: A comparison study between customer expectation and customer perceived at MAA Seremban / Sabariah Mahjar - Mahjar, Sabariah (Faculty of Business and Management, 2006)
The purpose of this research is to study the comparison between customer expectation and customer perceived at MAA. MAA company does realize that it is important to know the level of its customer expectation and its customer perceived in order for them to not only satisfied their customer but to also achieve the level of delighting their customers so thus the customers will become loyal. Understanding the customer expectation and perception of the actual performance also is important for MAA as to indicate their service quality level and performances in the eye of consumers. This paper consists of five chapters which explain the subject matter by stages. Chapter I explains the introduction, background of the study and theoretical framework which act as a guide to the research flow and process. Chapter 2 explains the literature review, which relates to the subject studied. Moving on to chapter 3, research methodology is explained, which consist of methods and sampling techniques used . Data findings and discussions is being detailed in chapter 4, gathered from the information obtained from respondents. And finally , chapter 5 consisted of results' summaries and findings, which explain conclusions and recommendations. The outcome from this research paper enabled to help the management to see whether the company's service quality is being delivered up to the customers' expectation or it is otherwise.